Digital Literacy on the Use of E-Module Towards Students’ Self-Directed Learning on Learning Process and Outcomes Evaluation Cources - Sanova, Aulia; Bakar, Abu; Afrida, Afrida; Kurniawan, Dwi Agus; Aldila, Febri Tia (Jurnal Pendidikan Indonesia, 2022)
The context of learning in the 4.0 revolution era is currently a challenge, especially in education at the university level. Creative learning processes need to be developed so that learning patterns need to be updated by placing students as learning subjects and applying more flexible learning media. This study aims to analyze the level of closeness of the relationship and see whether there is a simultaneous (together) and partial effect between digital literacy and students' self-directed learning. This research leads to quantitative research. The research instrument used was an open and closed questionnaire. The questionnaire used in this study was an open and closed questionnaire. The sample in this study was 33 students using the purposive sampling technique. The technique used to analyze the data is descriptive qualitative analysis, quantitative and inferential statistics. The results showed that there was a correlation that had a simultaneous effect. It can be concluded that there is a strong correlation level and has a simultaneous and partial influence between digital literacy and students' self-directed learning on the use of e-modules in evaluating the process and learning outcomes of courses. The use of e-modules can make it easier for students to learn and can improve independent learning in students.